Hasil Kajian Sintaksis Novel Selamat Tinggal Karya Tere Liye sebagai Bahan Ajar Mata Pelajaran Bahasa Indonesia - Fathia Rosyida; Sutrimah Sutrimah; Garwati Garwati (Jurnal Pendidikan Edutama, 2021)
Abstract: Novels can be interpreted as a form of literary work written by the author without releasing the intrinsic and extrinsic elements. For this reason, the purpose of this study is to find out 1) the form of phrases, clauses, and sentences in Tere Liye's novel entitled Selamat Tinggal 2) the results of the study of Tere Liye's novel entitled Selamat Tinggal can be used as teaching materials for Indonesian language subjects. This research is a qualitative research using listening, engaging, and proficient techniques starting from steps 1) preparation, 2) data collection, and 3) data analysis. The conclusions of this research are (1) Tere Liye's novel entitled Selamat Tinggal contains elements of phrases, clauses, and sentences. Phrases in Tere Liye's novel entitled Selamat Tinggal are verb phrases, noun phrases, adjective phrases, numeral phrases, endocentric phrases, and exocentric phrases. The clause in Tere Liye's novel entitled Selamat Tinggal is in the form of positive and negative clauses. Sentences in Tere Liye's novel entitled Selamat Tinggal are sentences based on 1) pronunciation, 2) grammatical structure or number of phrases, 3) function, 4) elements, 5) arrangement, 6) style or form of presentation, 7) subject. (2) The results of the study of Tere Liye's novel entitled Selamat Tinggal can be used as teaching materials for Indonesian language subjects from elementary to high school levels based on KI and KD at each level of education.Keywords: Novel entitled Selamat Tinggal, Tere Liye, Syntax, teaching material, Indonesian language subject  Abstrak: Novel dapat dimaknai sebagai bentuk karya sastra yang ditulis oleh pengarang dengan tidak melepaskan unsur intrinsik dan ekstrinsik. Untuk itu tujuan dari penelitian ini adalah ingin mengetahui 1) bentuk frasa, klausa, dan kalimat pada novel Selamat Tinggal karya Tere Liye, 2) hasil kajian novel Selamat Tinggal karya Tere Liye dapat dijadikan sebagai bahan ajar mata pelajaran bahasa Indonesia. Penelitian ini merupakan penelitian kualitatif dengan menggunakan teknik simak, libat, dan cakap dengan dimulai dari langkah 1) persiapan, 2) pengumpulan data, dan 3) analisis data. Simpulan penelitian ini adalah (1) Novel Selamat Tinggal karya Tere Liye mengandung Unsur frasa, klausa, dan kalimat. Frasa pada novel Selamat Tinggal karya Tere Liye berupa frasa verba, frasa nomina, frasa adjektiva, frasa numeralia, frasa endosentris, frasa eksosentris. Klausa pada novel Selamat Tinggal karya Tere Liye berupa klausa positif dan negatif. Kalimat pada novel Selamat Tinggal karya Tere Liye berupa kalimat yang didasarkan pada 1) pengucapan, 2) struktur gramatikal atau jumlah frasa, 3) fungsi, 4) unsur, 5) susunan, 6) gaya atau bentuk penyajian, 7) subjek. (2) Hasil kajian novel Selamat Tinggal karya Tere Liye dapat dijadikan sebagai bahan ajar mata pelajaran bahasa Indonesia mulai jenjang sekolah dasar hingga menengah atas berdasarkan KI dan KD pada setiap jenjang pendidikan tersebut. Kata Kunci: Novel Selamat Tinggal, Tere Liye, sintaksis, bahan ajar, mata pelajaran bahasa Indonesia